2009
DOI: 10.1007/s12011-009-8361-6
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity in Rat’s Brain Induced by Exposure of Manganese and Neuroprotective Effects of Pinacidil and Nimodipine

Abstract: Manganese (Mn) is an essential trace element for humans. However, manganism would be caused by excessive Mn. The mechanisms underlying excitotoxicity induced by manganism are poorly understood. As it is known to us, glutamate (Glu) is the most prevalent excitatory neurotransmitter. To determine the possible role of dysfunction of Glu transportation and metabolism in Mn-induced excitotoxicity, the rats were ip injected with different dose of MnCl(2) (0, 50, 100, and 200 micromol/kg), the levels of Mn and activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Neonatal rats exposed subcutaneously to lower levels of Mn for 4 weeks had increased levels of glutamate in the striatum and evident neurotoxicity that was prevented by MK-801 (Xu et al 2009), whereas studies in which monkeys were exposed intravenously to Mn reported no change in glutamate levels or glutamate receptor density (PUBMED ID 19520674). Additional studies using the neonatal rat model indicated that both pinacidil, a potassium channel agonist, and nimodipine, a Ca channel antagonist, reversed Mn neurotoxicity and loss of glutamine synthetase activity, further implicating excitotoxicity in the mechanism of Mn-induced basal ganglia injury (Deng et al 2009). A role for early dysfunction of astrocytes is also supported by data in Mn-exposed animals demonstrating changes in markers of astrocyte activation, such as S β 100 and the peripheral benzodiazepine receptor, prior to any evident neuronal lesion (Hazell et al 2003; Henriksson and Tjalve 2000).…”
Section: Neuropathological Characteristics Of Mn Exposurementioning
confidence: 99%
“…Neonatal rats exposed subcutaneously to lower levels of Mn for 4 weeks had increased levels of glutamate in the striatum and evident neurotoxicity that was prevented by MK-801 (Xu et al 2009), whereas studies in which monkeys were exposed intravenously to Mn reported no change in glutamate levels or glutamate receptor density (PUBMED ID 19520674). Additional studies using the neonatal rat model indicated that both pinacidil, a potassium channel agonist, and nimodipine, a Ca channel antagonist, reversed Mn neurotoxicity and loss of glutamine synthetase activity, further implicating excitotoxicity in the mechanism of Mn-induced basal ganglia injury (Deng et al 2009). A role for early dysfunction of astrocytes is also supported by data in Mn-exposed animals demonstrating changes in markers of astrocyte activation, such as S β 100 and the peripheral benzodiazepine receptor, prior to any evident neuronal lesion (Hazell et al 2003; Henriksson and Tjalve 2000).…”
Section: Neuropathological Characteristics Of Mn Exposurementioning
confidence: 99%
“…Several mechanisms are under discussion, such as ROS generation, imbalancing Fe II/Fe III homeostasis, mitochondrial damage or impaired glutamate homeostasis in brain [48]. Binding of Mn 2+ can also inhibit Glutamine synthetase, a 352 kDa, essential Mn-enzyme [1,50] in brain, and though probably affect glutamate homeostasis in brain directly [51]. Since however the HMM Mn fraction represents only a minor percentage this mechanism seem to be of subordinate importance only.…”
Section: Mn Species Characterization With Sec-icp-msmentioning
confidence: 99%
“…The FDA-approved anti-hypertensive drugs, pinacidil and cromakalim, are also neuroprotective as K ATP activators (Deng et al, 2009;Lauritzen et al, 1997;Shukry et al, 2015;Wang et al, 2011). Even brief application of K ATP openers, including diazoxide, Ipt, pinacidil, and cromakalim, can be neuroprotective against rotenone and/or MPP + -induced cell death in PD models (Tai and Truong, 2002;Yang et al, 2004;Yang et al, 2005a Zhou et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%